Partial Vaginectomy, Complete Vaginectomy, Partial Vestibule-Vaginectomy, Vulvo-Vestibule-Vaginectomy and Vulvo-Vestibulectomy: Different Surgical Procedure in Order to Better Approach Vaginal Diseases - Daniele Zambelli; Simona Valentini; Giulia Ballotta; Marco Cunto (Animals, 2022)
Total or partial vulvo-vaginectomy or vaginectomy are not routinely performed due to the complexity of the techniques and because they are considered radical treatments. Little information can be found in the literature, as the same technique is often named in a different way by different authors, confusing the reader. Therefore, the aim of this essay is to describe five different surgical techniques: partial vaginectomy, complete vaginectomy, partial vestibule-vaginectomy, vulvo-vestibule-vaginectomy and vulvo-vestibulectomy. All techniques are described on the basis of the correct identification of the anatomical nomenclature related to structures involved in surgery, in order to give a more precise and unambiguous description and execution of surgical techniques. Moreover, possible intraoperative and perioperative complications and the authors’ clinical experience in 33 dogs are described. All techniques are well tolerated and could be curative in case of benign or malignant tumours that have not yet metastasized and palliative in other cases. Moreover, they are also useful for therapeutic purposes for chronic vaginitis, severe vaginal cysts or congenital abnormalities. It is our opinion that having five different available techniques to approach vaginal disease is useful to perform the best surgery according to the clinical findings, patient’s characteristics, technique invasiveness and whether it is palliative or not.